Early Information Needs of Adolescents and Young Adults about Late Effects of Cancer Treatment - Greenzang, Katie A. (Cancer, 2020)
BACKGROUND: Adolescents and young adult (AYA) cancer survivors have high risks of late effects. Little is known about AYA late effect information needs early in treatment or their role in treatment decision-making. We evaluated the importance, quality, and implications of information about late effects in AYAs recently diagnosed with cancer. METHODS: We surveyed 201 AYAs with cancer age 15–29 years, treated at Dana-Farber Cancer Institute, Boston, MA. Patients were approached within 6 weeks of diagnosis and asked about their late effect and infertility information needs, treatment decision-making, and communication outcomes. RESULTS: 45% of participants were female; 88% were white. Most AYAs (87%, 174/201) considered information about the risks of late effects to be extremely or very important; 80%(159/201) valued information about infertility. Many were distressed by information about late effects (53%, 105/201) and infertility (45%, 90/201); those who considered late effects information distressing were more likely to value this information (P<0.0001). Consideration of late effects (41%, 82/202) and infertility (36%, 72/202) greatly influenced many patients’ treatment decision-making. Whereas 92% (184/199) of patients reported receiving high-quality information about diagnosis, 57%(113/199, P<0.0001) felt they received high-quality information about late effects, and 65%(130/199, P<0.0001) about infertility. CONCLUSIONS: Most AYAs with cancer value early information about risks of late effects and infertility, yet many patients felt they did not receive high-quality information about these topics. Development of age-appropriate late effect communication strategies that recognize high AYA distress may help address the gap between desired information and perceived information quality.